Biostratigraphy and Climate Change in the Late Miocene Age Based on Foraminifera in the Oyo Formation, Oyo River Section, Gunung Kidul, Yogyakarta - Adesti Audina Ulfah; Akmaluddin Akmaluddin; Didit Hadi Barianto (Journal of Tropical Biodiversity and Biotechnology, 2023)
The date of the paleoclimate event was ascertained using a biostratigraphic analysis. The thickness of the Oyo Formation was measured using measurements with a Jacob stick method, yielding a thickness of 80.8 meters and 23 rock samples. In the Southern Mountains Zone,  new result of the age of the upper part of the Oyo Formation by biostratigraphy investigation of the hill Late Miocene (9.79 Ma to 5.78 Ma). Biostratigraphic investigation in the Oyo River revealed 28 species and 9 genera, with two datums. The study area was classified into three biozonations based on the datum found Globorotalia acostaensis/M13a/N16 zone, the lower Globorotalia plesiotumida/M13b/N17 zone, and the upper Globigerinoides conglobatus/M14/N17 zone. The results of a paleoclimate analysis on the Oyo River Section show a general cooling tendency in the study area. Seven paleoclimate zones can be determined from these trends consisting of four warm and three cold zones. Zone I (warm), zone II (cold), zone III (warm), and zone IV (cold) have the coldest peak in the study region in 8.3 Ma, zone V (warm), and zone VI (cold), followed by zone VII (warm). Based on the correlation with other studies (South China Sea, Pacific Ocean, Oyo River, Ngalang River, and Ngioro Section), paleoclimate events in the study area occur globally.